Violence and discrimination against transgender people in legal case Azul Rojas Marín v. Peru - Ramírez Bernal, Víctor Raúl Jesús (2023)
The objective of this research is to show that the IACHR judgement in the case of Azul Rojas Marín vs. Peru develops relevant aspects regarding violence and discrimination against trans people on the basis of the Istanbul Protocol, and non-relevant aspects regarding the reparations imposed. The problem with the judgment under analysis concerns the irrelevant aspects of the reparations imposed, as they were ordered without further analysis of the reality. Non-violence and discrimination against trans people will be developed, as well as the relevant and non-relevant aspects of the judgment under analysis on the basis of the Istanbul Protocol. The methodology used was based on documentary, legal and national and international case law analysis. The result of the research was to identify the positive and negative points of the judgment under analysis. The conclusion is that the IACHR ruling is an important precedent in the fight against violence and discrimination against transgender people in Peru and the world.